Lifshitz Transitions Induced by Temperature and Surface Doping in Type‐II Weyl Semimetal Candidate Td‐WTe2 (Phys. Status Solidi RRL 12/2017). Issue 12 (14th December 2017) - Zhang, Qihang; Liu, Zhongkai; Sun, Yan; Yang, Haifeng; Jiang, Juan; Mo, Sung‐Kwan; Hussain, Zahid; Qian, Xiaofeng; Fu, Liang; Yao, Shuhua; Lu, Minghui; Felser, Claudia; et al.
Abstract : Raising the Weyl Fermi sea level: Tungsten ditelluride in distorted 1T structure (Td ‐WTe2 ) has been discovered to be a type‐II Weyl semimetal that harbors strongly tilted Weyl cones. In their Letter (article no.1700209 ), using high‐resolution angle‐resolved photoemission spectroscopy (ARPES), Qihang Zhang et al. systematically investigate the electronic structure of Td ‐WTe2 and its evolution with temperature and surface decoration. Their ARPES measurements together with ab initio calculations support the existence of a type‐II TWS (topological Weyl semimetal) phase at low temperature. Using temperature regulation and surface modification, they have successfully raised the Fermi sea level and realized two‐stage Lifshitz transition. That is, the topology of the Fermi surface of Td ‐WTe2 changes twice with temperature increasing or surface K‐doping. These findings not only help us understand the intriguing physical properties of Td ‐WTe2, but also provide a promising method to manipulate the electron's behavior and physical properties in type II TWS. The cover image vividly shows the Fermi sea. From left to the right, the color changing indicates the temperature increasing and the "Weyl cone" only exists at low temperature. The "raining" represents the surface electron doping. The lattice in the bottom of the Fermi sea indicates that the results are obtained on WTe2 .